Organic hole transport material doped with acid-base byproducts and optical device using the same
By using acid and base by-products as dopants in perovskite solar cells, the physical characteristics of PTAA are improved, and the problem of low stability of perovskite solar cells is solved, and perovskite optical devices with high efficiency and high durability are achieved.
Patent Information
- Application Number
- CN202180021231.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-07-09
- Filing Date
- 2021-07-09
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2041-07-09
AI Technical Summary
Perovskite solar cells are unstable in terms of light, heat and humidity, especially when using organic hole transport substances, their stability is greatly reduced.
By using acid and base by-products as dopants, the physical properties of poly(triarylamine) (PTAA) are improved, and their hole mobility and durability are improved, forming a perovskite optic with high efficiency and high durability.
It is achieved to improve the hole mobility and durability of PTAA without using additional dopants, thereby improving the efficiency and stability of perovskite optics.
Smart Images

Figure CN115280532B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an organic hole transport material using a dopant obtained from an acid-base by-product and an optical device using the same. Background Art
[0002] The need to develop environmentally friendly and sustainable energy technologies that can cope with climate change is increasing. Optical devices include photoelectric conversion devices and electro-optical conversion devices. Solar cells, one of the photoelectric conversion devices, have attracted much attention as a sustainable energy technology and a solution that can actively cope with future energy needs. Solar cells are the most basic unit of solar power generation and are semiconductor devices that convert solar energy into electrical energy, using the photovoltaic effect.
[0003] However, today's solar cell technology has not shown enough efficiency to replace future energy needs, so technological innovation beyond the current level of technology is needed. In response to this, technologies based on innovative materials such as dye-sensitized solar cells, organic solar cells, quantum dot solar cells, and perovskite solar cells (PSC) have been developed as new generation solar cells.
[0004] Among them, perovskite solar cells have become one of the pillars of thin-film solar cells that can replace traditional silicon solar cells. Perovskite solar cells, which include hole transport materials, light absorbing materials, and electron transport materials, use perovskite as a light absorbing material, which shows a significant photovoltaic effect.
[0005] However, perovskite solar cells have many limitations due to their instability to light, heat, and humidity. For example, problems such as decomposition due to moisture, thermal instability, oxygen-induced defects, and instability of hole transport materials (HTM) have been confirmed. In particular, when organic hole transport materials are used, the stability of solar cells is greatly reduced.
[0006] Therefore, various techniques have been developed to improve the stability of perovskite solar cells, but there have been relatively few attempts to develop stable hole-transporting species using dopants. Summary of the invention
[0007] Problem that the invention aims to solve
[0008] According to an embodiment of the present invention, a poly(triarylamine) (PTAA) having high efficiency and high durability is provided.
[0009] According to an embodiment of the present invention, a perovskite optical device having high efficiency and high durability is provided.
[0010] According to an embodiment of the present invention, the physical properties of PTAA are improved by using acid-base byproducts.
[0011] According to an embodiment of the present invention, by using acid-base byproducts having good dispersibility as PTAA dopants, the hole mobility of PTAA is improved in the absence of other dopants.
[0012] Means used to solve problems
[0013] According to an embodiment of the present invention, the organic hole transport material is doped with an acid-base byproduct, wherein the acid-base byproduct is formed by an acid-base reaction between an acid and a base, wherein the acid includes a hydrogen ion (H+).
[0014] According to one embodiment of the present invention, the acid has a chemical formula H + X - , H + Corresponding to hydrogen ions, X - corresponds to anions.
[0015] According to an embodiment of the present invention, X - Corresponding to TFSI - .
[0016] According to an embodiment of the present invention, the base includes any one of primary amine, secondary amine, tertiary amine or a combination thereof.
[0017] According to an embodiment of the present invention, an optical device includes the above-mentioned organic hole transport material.
[0018] Effects of the Invention
[0019] According to various embodiments of the present invention, a PTAA doped with acid-base byproducts having high efficiency and high durability is provided.
[0020] Furthermore, according to various embodiments of the present invention, a perovskite optical device having high efficiency and high durability is provided.
[0021] Furthermore, according to various embodiments of the present invention, a PTAA doped with acid-base byproducts is provided.
[0022] Furthermore, according to various embodiments of the present invention, the hole mobility of PTAA can be improved by using acid-base byproducts that have good dispersibility themselves as dopants without the need for additional dopants.
[0023] Furthermore, according to various embodiments of the present invention, by doping only one dopant into PTAA, the hole mobility and durability of PTAA may be simultaneously improved.
[0024] The effects of the present invention are not limited to the above-mentioned effects, and those skilled in the art can clearly understand other unmentioned effects based on the description of the claims. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Embodiments of the present invention will be described with reference to the drawings described below, wherein like reference numerals refer to like elements, but are not limited thereto.
[0026] Figure 1 is a diagram showing a perovskite optical device according to the prior art.
[0027] Figure 2 is a diagram of a perovskite optical device according to an embodiment of the present invention.
[0028] Figure 3 1 is a current-voltage characteristic diagram according to an embodiment of the present invention and a comparative example. DETAILED DESCRIPTION
[0029] The terms used in the present invention will be briefly described below, and the disclosed embodiments will be described in detail. The terms used in this specification have been selected as much as possible from currently widely used general terms while considering the functions in the present invention, but these may change according to the intentions of those skilled in the art or precedents, the emergence of new technologies, etc. In addition, in certain cases, there are also terms arbitrarily selected by the applicant, in which case, their meanings will be described in detail in the corresponding description section of the present invention. Therefore, the terms used in the present invention should be defined according to the meaning of the terms and the full content of the present invention, rather than being defined according to simple term names.
[0030] In the present invention, an expression in a singular form includes a plural expression unless it is clearly determined as a singular in the context. In addition, a plural expression includes a singular expression unless it is clearly determined as a plural in the context.
[0031] In the present invention, when a certain part includes a certain constituent element, unless otherwise stated, it means that other constituent elements may be further included, rather than excluding other constituent elements.
[0032] In the present invention, the term "A and / or B" means A, B, or A and B.
[0033] The terms "about" and the like expressing the degree used in the present invention mean that when there is a permissible error, the permissible error is included.
[0034] In the present invention, the term "at least any one" included in the Markush form expression means one or more selected from the group consisting of the constituent elements described in the Markush form expression.
[0035] In the present invention, "perovskite" or "PE" refers to a substance having a perovskite crystal structure, and may have various perovskite crystal structures in addition to the ABX3 crystal structure.
[0036] In the present invention, the term "optical device" is used to refer to a photoelectric conversion device and an electro-optical conversion device. For example, an optical device includes but is not limited to a solar cell, a light emitting diode (LED), a photodetector, an X-ray detector, and a laser.
[0037] In the present invention, the term "halide", "halogen", "halogenide halide" or "halo" refers to a substance or composition containing a halogen atom belonging to Group 17 of the periodic table in the form of a functional group, for example, it may include a chlorine compound, a bromine compound, a fluorine compound or an iodine compound.
[0038] In the present invention, the term "layer" refers to a layer shape having a thickness. The layer may correspond to porosity or non-porosity. Porosity means having porosity. The layer as a whole may have a bulk shape or correspond to a single crystal thin film, but is not limited thereto.
[0039] In the present invention, when one component is located “on” another component, unless otherwise specified, this includes not only a case where one component is in contact with the other component but also a case where the other component exists between the two components.
[0040] In the present invention, when efficiency is recorded only without additional description, the efficiency refers to power conversion efficiency (PCE).
[0041] Hereinafter, specific contents for implementing the present invention will be described in detail with reference to the accompanying drawings. However, in the following description, if there is a risk of unnecessarily obscuring the gist of the present invention, the detailed description of well-known functions or configurations will be omitted.
[0042] The advantages and features of the embodiments of the present invention, as well as methods for achieving them, will become clear through the embodiments described together with reference to the following drawings. However, the present invention is not limited to the embodiments disclosed below, but can be implemented in various different forms, and these embodiments are provided only to complete the disclosure and fully inform the scope of the invention to those skilled in the art.
[0043] In the accompanying drawings, the same or corresponding constituent elements are given the same reference numerals. In addition, in the description of the following embodiments, the repeated description of the same or corresponding constituent elements may be omitted. However, even if the description of the constituent elements is omitted, it does not mean that these constituent elements are not included in certain embodiments.
[0044] According to an embodiment of the present invention, an optical device may include a first electrode, a first charge transport layer formed on the first electrode, a perovskite layer formed on the first charge transport layer, a second charge transport layer formed on the perovskite layer, and a second electrode formed on the second charge transport layer.
[0045] For example, when the optical device is used for a solar cell having a nip structure, the optical device may have a structure in which a first electrode, an electron transport layer, a perovskite layer, a hole transport layer, and a second electrode are stacked in sequence. Alternatively, when the optical device corresponds to a solar cell having a pin structure, the solar cell may have a structure in which a first electrode, a hole transport layer, a perovskite layer, an electron transport layer, and a second electrode are stacked in sequence.
[0046] For example, the optical device can have a planar structure, a bi-layer structure, or a meso-superstructure. The shapes of the electrodes, charge transport layers, and perovskite layers will be deformed according to the structure of the optical device.
[0047] For example, when the optical device has a double-layer structure, the perovskite layer may be a double-layer structure formed in a layer shape by filling porous TiO2 with perovskite. The double-layer may refer to a structure consisting of a first layer of a TiO2:perovskite mixed layer in which all pores of porous TiO2 are filled with perovskite and a second layer of a pure perovskite layer located thereon.
[0048] The electrode includes a first electrode and / or a second electrode, which may be an anode or a cathode. The electrode may be an anode or a cathode. When the first electrode is an anode, the second electrode may be a cathode. For example, the electrode may be a conductive oxide such as indium-tin oxide (ITO) or indium-zinc oxide (IZO), fluorine-doped tin oxide (FTO), etc. Alternatively, the electrode may be a substance selected from the group consisting of silver (Ag), gold (Au), magnesium (Mg), aluminum (Al), platinum (Pt), tungsten (W), copper (Cu), molybdenum (Mo), nickel (Ni), palladium (Pd), chromium (Cr), calcium (Ca), samarium (Sm) and lithium (Li) and combinations thereof. Alternatively, the electrode may correspond to a material obtained by doping a conductive substance into a flexible transparent material such as plastic, such as polyethylene terephthalate (PET), polyethylenenaphthelate (PEN), polypropylene (PP), polyimide (PI), polycarbonate (PC), polystyrene (PS), polyoxyethylene (POM), etc.
[0049] The electrode may correspond to a substance that is commonly used as an electrode material for a front electrode or a back electrode in an optical device. The electrode may be one or more substances selected from gold, silver, platinum, palladium, copper, aluminum, carbon, cobalt sulfide, copper sulfide, nickel oxide, and a composite thereof, but is not limited thereto. For example, the electrode may correspond to any one or more inorganic conductive electrodes selected from fluorine doped tin oxide (FTO; Fouorine doped Tin Oxide), indium doped tin oxide (ITO; Indium doped Tin Oxide), zinc oxide (ZnO), carbon nanotubes (CNT) and graphene, or an organic conductive electrode such as poly (3,4-ethylenedioxythiophene) -poly (styrene sulfonic acid) (PEDOT: PSS), but is not limited thereto.
[0050] As a charge transport layer, an electron transport layer (ETL) or a hole transport layer (HTL) may be formed on the first electrode. When the first charge transport layer is an electron transport layer, the second charge transport layer may correspond to the hole transport layer. Alternatively, when the first charge transport layer is a hole transport layer, the second charge transport layer may correspond to the electron transport layer.
[0051] The electron transport layer may correspond to a semiconductor including an "n-type substance". "N-type substance" refers to an electron transport substance. The electron transport substance may be a single electron transport compound or element substance, or may be a mixture of two or more electron transport compounds or element substances. The electron transport compound or element substance may be undoped or doped with one or more dopant elements.
[0052] For example, the electron transport layer may be an electron conductive organic layer or an electron conductive inorganic layer. The electron conductive organic material may be an organic material used as an n-type semiconductor in a common organic solar cell. For example, the electronically conductive organic matter may include fullerene (C60, C70, C74, C76, C78, C82, C95); fullerene derivatives including PCBM ([6,6]-phenyl-C61-butyric acid methyl ester), C71-PCBM ([6,6]-phenyl-C71-butyric acid methyl ester), C84-PCBM ([6,6]-phenyl-C84-butyric acid methyl ester), PC70BM ([6,6]-phenyl C70-butyric acid methyl ester); PBI (polybenzimiadzole); PTCBI (3,4,9,10-perylenetetracarboxylic acid bisbenzimidazole); F4-TCNQ (tetrafluorotetracyanoquinodimethane); or mixtures thereof, but are not limited thereto.
[0053] The electronically conductive inorganic substance may be an electronically conductive metal oxide used for electron transport in a conventional quantum dot-based solar cell, a dye-sensitized solar cell, or a perovskite-based solar cell. In one embodiment, the electronically conductive metal oxide may be an n-type metal oxide semiconductor. For example, the n-type metal oxide semiconductor may be selected from titanium (Ti) oxide, zinc (Zn) oxide, indium (In) oxide, tin (Sn) oxide, tungsten (W) oxide, niobium (Nb) oxide, molybdenum (Mo) oxide, magnesium (Mg) oxide, barium (Ba) oxide, zirconium (Zr) oxide, strontium (Sr) oxide, Yr oxide, lanthanum (La) oxide, vanadium (V) oxide, aluminum (Al) oxide, yttrium (Y) oxide, scandium (Sc) oxide, samarium (Sm) oxide, gallium (Ga) oxide, indium (In) oxide, and strontium titanium (SrTi) oxide, one or more substances, mixtures thereof, or composites thereof, but are not limited thereto.
[0054] The electron transport layer can be a dense layer (dense film) or a porous layer (porous film). The dense electron transport layer can be a film of the above-mentioned electron conductive organic matter or a dense film of the electron conductive inorganic matter. The electron transport layer of the porous film can be a porous film composed of particles of the above-mentioned electron conductive inorganic matter.
[0055] The hole transport layer may correspond to a semiconductor including a "p-type substance". "P-type substance" refers to a hole transporting substance. The hole transporting substance may be a single hole transporting compound or elemental substance, or a mixture of two or more hole transporting compounds or elemental substances. The hole transporting compound or elemental substance may be undoped or doped with one or more dopant elements. The hole transporting substance may be an organic hole transporting substance, an inorganic hole transporting substance, or a combination thereof.
[0056] The hole transport layer can be manufactured by a solution process. The hole transport layer can be a thin film of an organic hole transport material. The thickness of the hole transport layer thin film can be 10 to 500 nm, but is not limited thereto.
[0057] The hole transport material may correspond to an organic hole transport material, specifically, may correspond to a single molecule to a high molecular organic hole transport material (hole conductive organic matter). As a high molecular organic hole transport material, it may include one or more substances selected from thiophene, p-phenylene vinylene, carbazole and triphenylamine.
[0058] The single molecule to low molecular organic hole transport material may include pentacene, coumarin 6 (3-(2-benzothiazolyl)-7-(diethylamino)coumarin), zinc phthalocyanine (ZnPC), copper phthalocyanine (CuPC), titanium oxide phthalocyanine (TiOPC), and phthalocyanine), Spiro-MeOTAD (2,2',7,7'-tetrakis(N,Np-dimethoxyphenylamino)-9,9'-spirobifluorene), copper(II)1,2,3,4,8,9,10,11,15,16,17,18,22,23,24,25-hexadecafluoro-29H,31H-phthalocyanine), subphthalocyanine (SubPc, boron subphthalocyanine chloride), The invention can be one or more of, but not limited to, N3 (cis-di(thiocyanato)-bis(2,2'-bipyridyl-4,4'-dicarboxylic acid)-ruthenium(II)).
[0059] The polymer organic hole transport material can be selected from poly(3-hexylthiophene) (P3HT), poly(2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylenevinylene (MDMO-PPV, poly[2-methoxy-5-(3',7'-dimethyloctyloxyl)]-1,4-phenylenevinylene), poly[2-methoxy-5-(2"-ethylhexyloxy)-p-phenylenevinylene] (MEH-PPV, poly[2-methoxy-5-(2"-ethylhexyloxy)-p-phenylene vinylene]), poly(3-octylthiophene) (P3OT, poly(3-octylthiophene)), poly(octylthiophene) (POT, poly(octylthiophene)), poly(3-decylthiophene) (P3DT, poly(3-decylthiophene) thiophene)), poly(3-dodecylthiophene) (P3DDT), poly(p-phenylene vinylene) (PPV), poly(9,9'-dioctylfluorene-co-N-(4-butylphenyl)diphenylamine (TFB), polyaniline, 2,22',7,77'-tetrakis(N,N-di-p-methoxyphenylamine)-9,9,9'-spirobifluorene (SpiroMeOTAD, 2,22',7,77'-tetrkis(N,N-di-p-methoxyphenylamine)-9,9,9'-spirobi fluorine), poly[2,1,3-benzothiadiazole-4,7-diyl[4,4-bis(2-ethylhexyl-4H-cyclopenta[2,1-b:3,4-b']dithiophene-2,6-diyl]] (PCPDTBT, Poly[2,1,3-benzothiadiazole-4,7-diyl[4,4-bis(2-ethylhexyl-4H-cyclopenta[2,1-b:3,4-b']dithiophene-2,6-diyl]), poly[(4,4'-bis(2-ethylhexyl)dithieno[3,2-b:2',3'-d]silole)-2,6-diyl-alt-(2,1,3-benzothiadiazole)-4,7-diyl] (Si-PCPDTBT, poly[(4,4′-bis(2-ethylhexyl)dithieno[3,2-b:2′,3′-d]silole)-2,6-diyl-alt-(2,1,3-benzothiadiazole)-4,7-diyl]), poly((4,8-diethylhexyloxy)benzo([1,2-b:4,5-b']dithiophene)-2,6-diyl)-alt-((5-octylthieno[3,4-c]pyrrole-4,6-dione)-1,3-diyl) )-2,6-diyl)-alt-((5-octylthieno[3,4-c]pyrrole-4,6-dione)-1,3-diyl)), poly[2,7-(9-(2-ethylhexyl)-9-hexyl-fluorene)-alt-5,5-(4',7,-di-2-thienyl-2',1',3'-benzothiadiazole)] (PFDTBT, poly[2,7-(9-(2-ethylhexyl)-9-hexyl-fluorene)-alt-5,5-(4',7,-di-2-thienyl-2',1',3'-benzothiadiazole)]), poly[2,7- PFO-DBT, poly[2,7-9,9-(dioctyl-fluorene)-alt-5,5-(4',7'-di-2-thienyl-2',1',3'-benzothiadiazole)]), PSiFDTBT, poly[(2,7-dioctylsilafluorene)-2,7-diyl-alt-(4,7-bis(2-thienyl)-2,1,3-benzothiadiazole)-5,5′-diyl] -2,7-diyl-alt-(4,7-bis(2-thienyl)-2,1,3-benzothiadiazole)-5,5′-diyl]), poly[(4,4′-bis(2-ethylhexyl)dithieno[3,2-b:2′,3′-d]silole)-2,6-diyl-alt-(2,1,3-benzothiadiazole)-4,7-diyl] (PSBTBT, poly[(4,4′-bis(2-ethylhexyl)dithieno[3,2-b:2′,3′-d]silole)-2,6-diyl-alt-(2,1,3-benzothiadiazole)-4,7-diyl]7-diyl]), Poly[[9-(1-octylnonyl)-9H-carbazole-2,7-diyl]-2,5-thiophenediyl-2,1,3-benzothiadiazol-4,7-diyl-2,5-thiophenediyl] (PCDTBT, Poly[[9-(1-octylnonyl)-9H-carbazole-2,7-diyl]-2,5-thiophenediyl-2,1,3-benzothiadiazol e-4,7-diyl-2,5-thiophenediyl]), poly(9,9′-dioctylfluorene-co-bis(N,N′-(4,butylphenyl))bis(N,N′-phenyl-1,4-phenylene)diamine (PFB, poly(9,9′-dioctylfluorene-co-bis(N,N′-(4,butylphenyl))bis(N,N′-phenyl-1,4-phenylene) ene)diamine), poly(9,9'-dioctylfluorene-co-benzothiadiazole) (F8BT, poly(9,9'-dioctylfluorene-co-benzothiadiazole), poly(3,4-ethylenedioxythiophene) (PEDOT, poly(3,4-ethylenedioxythiophene)), poly(3,4-ethylenedioxythiophene) poly(styrenesulfonate)) (PEDOT:PSS, poly(3,4-ethylenedioxythiophene) poly(styrenesulfonate)), poly(triarylamine) (PTAA, poly(triarylamine)), poly(4-butylphenyldiphenyl-amine)), and one or more of their copolymers, but not limited thereto.
[0060] An additional description will be given additionally for the hole transport layer.
[0061] The electron transport layer or the hole transport layer may correspond to the buffer layer, or may include the buffer layer. The electron transport layer or the hole transport layer may use a dopant to improve the surface. The electron transport layer or the hole transport layer may be applied to one side of the electrode by spin coating, dip coating, inkjet printing, gravure printing, spray coating, rod coating, gravure coating, brush coating, thermal evaporation, sputtering, electron beam, screen printing, scraper process, etc. or applied in the form of a thin film.
[0062] The perovskite layer may be formed to directly contact the first electrode. Alternatively, the perovskite layer may be formed to directly contact the electron transport layer or the hole transport layer. The perovskite layer includes perovskite.
[0063] The perovskite layer can be formed by various processes including a vapor deposition process or a solution process. The perovskite layer can be formed using a vapor deposition process. The vapor deposition process can correspond to a process in which a substance is supplied into a vacuum chamber in a vaporized state or a plasma state, and the substance is deposited on the surface of a target object (e.g., a substrate). The perovskite layer can be formed by a coating process in a solution process. The coating process can be selected from the group consisting of spin coating, rod coating, nozzle printing, spray coating, slit die coating, gravure printing, inkjet printing, screen printing, electrohydrodynamic jet printing, electrostatic spraying, and a combination thereof, but is not limited thereto.
[0064] For example, the perovskite may include monovalent organic cations, divalent metal cations and halogen anions. In one embodiment, the perovskite of the present invention may satisfy the following chemical formula.
[0065] [Chemical formula 1]
[0066] AMX3
[0067] In Chemical Formula 1, A is a monovalent cation, which may correspond to an organic ammonium ion, an amidinium group ion, or a combination of an organic ammonium ion and an amidinium group ion.
[0068] For example, the organic cation as A may have the chemical formula (R1R2R3R4N) + In this case, R1 to R4 may correspond to hydrogen, unsubstituted or substituted C1-C20 alkyl, or unsubstituted or substituted aryl.
[0069] For example, the organic cation as A may have the formula (R5NH3) + , in which case R5 may correspond to hydrogen, or a substituted or unsubstituted C1-C20 alkyl group.
[0070] For example, the organic cation A has the chemical formula (R6R7N=CH-NR8R9) + , in which case R6 to R9 may correspond to hydrogen, methyl or ethyl.
[0071] Furthermore, A, as a monovalent metal ion, may correspond to an alkali metal ion.
[0072] For example, the monovalent metal ion A may correspond to Li + 、Na + , K + , Rb + , or Cs + ion.
[0073] Furthermore, A may correspond to a combination of a monovalent organic cation and a monovalent metal ion.
[0074] For example, A may correspond to a morphology of monovalent organic cations doped with monovalent metal ions. The monovalent metal ions used as doped metal ions may include alkali metal ions, which may be selected from Li + 、Na + , K + , Rb + , and Cs + One or more ions.
[0075] M may be a divalent metal ion. For example, M may include a 2+ 、Ni 2+ 、Co 2+ , Fe 2+ , Mn 2+ Cr 2+ , Pd 2+ 、Cd 2+ ,Ge 2+ Sn 2+ , Pb 2+ Yb 2+ and combinations thereof, but are not limited thereto.
[0076] X may correspond to a halogen ion. For example, the halogen ion may include a halogen ion selected from I - Br - , F-, Cl- and combinations thereof, but are not limited thereto.
[0077] For example, the perovskite may be any one or more mixtures selected from CH3NH3PbI3 (methylammonium lead iodide (MAPbI3)) and CH(NH2)2PbI3 (formamidinium lead iodide (FAPbI3)).
[0078] Furthermore, X may correspond to an oxygen ion.
[0079] Hereinafter, the hole transport material included in the hole transport layer according to an embodiment of the present invention will be described in more detail.
[0080] Optical devices exposed to strong sunlight can have their temperature rise to over 80°C, so materials with guaranteed thermal stability are needed. In particular, organic hole transport materials are known to be most susceptible to degradation due to heat. Therefore, an object of the present invention is to provide an organic hole transport material that can maintain high efficiency while ensuring stability against degradation factors.
[0081] The hole transport material contained in the hole transport layer can transport holes from the perovskite layer to the electrode. The hole transport material can be an organic hole transport material, an inorganic hole transport material, or a stacked material thereof. In one embodiment, the hole transport layer may include an organic hole transport material having excellent hole mobility characteristics. The organic hole transport layer may include an organic hole transport material, specifically, may include a single molecule to a high molecular organic hole transport material (hole conductive organic matter).
[0082] According to an embodiment of the present invention, the organic hole transport material may correspond to a polymer hole transport material including an additive obtained from an acid-base byproduct, for example, may correspond to PTAA (poly(triarylamine)).
[0083] Widely used single-molecule-based hole transport materials such as spiro-MeOTAD crystallize at lower temperatures, causing changes in electrical properties, which can reduce device efficiency. In contrast, polymer hole transport materials such as PTAA have higher thermal stability than single-molecule materials.
[0084] Since the conductivity of organic-based hole transport materials is low, in order to improve physical properties such as hole mobility, bis(trifluoromethane)sulfonimide lithium salt (hereinafter referred to as "LiTFSI") and 4-tert-butylpyridine (hereinafter referred to as "tBP") can be doped or added to PTAA as dopants or additives. LiTFSI acts as a p-dopant to increase the hole mobility of the hole transport material, and tBP hinders the aggregation of LiTFSI, so that LiTFSI is evenly dispersed in the hole transport material.
[0085] When LiTFSI is used as an additive to improve the hole mobility of PTAA, tBP must be used to improve the dispersibility because of its low dispersibility in organic solvents. The use of tBP helps dispersibility and thus has a positive effect on efficiency, but if the stress of high temperature conditions is applied, it will become a cause of efficiency decline.
[0086] In other words, despite the positive effects of additives on hole transport materials, LiTFSI and tBP may become the main components that cause instability in optical devices. LiTFSI is hygroscopic, so it can absorb water and accelerate the decomposition of perovskite. tBP easily evaporates, forming voids in the hole transport layer, or reacts with perovskite to cause chemical corrosion of perovskite.
[0087] Therefore, as a solution to the above problem, according to the hole transport material of one embodiment of the present invention, in order to increase the hole mobility in the hole transport material and improve the durability of the hole transport material, an acid-base byproduct with good dispersibility can be added as an additive to the polymer hole transport material (such as PTAA). The new acid-base byproduct replacing LiTFSI can not only improve the hole mobility, but also has good dispersibility in organic solvents, without the need for additional additives, thereby preventing the phenomenon of efficiency reduction at high temperatures.
[0088] According to an embodiment of the present invention, the acid-base byproduct added to the polymer hole transport material, such as PTAA, can be produced by an acid-base reaction between an acid and a base.
[0089] Acids can contain hydrogen ions (H + For example, an acid may be one that is ionized to produce hydrogen ions H + A substance that accepts a lone electron pair. An acid can satisfy Formula 2, in which case H + can correspond to a hydrogen ion, and X- can correspond to an anion.
[0090] [Chemical formula 2]
[0091] H + X -
[0092] For example, the acid according to an embodiment of the present invention may be any one of HTFSI, HCl, HBr, HI, or a combination thereof.
[0093] For example, the acid according to an embodiment of the present invention may satisfy Chemical Formula 3.
[0094] [Chemical formula 3]
[0095]
[0096] X in acid -It plays an important role not only in the performance of solar cells, but also in the charge transport properties of hole transport materials. For example, the conductivity of doped p-type conductive polymers is greatly affected by X-. For example, X- can correspond to TFSI - TFSI - Anions are highly conductive to electrical conduction. Figure 3 As shown, the charge collection process in the hole transport material layer can be promoted.
[0097] A base may be one that is ionized to accept hydrogen ions H + A substance that provides a lone electron pair or a substance that provides a lone electron pair. For example, the base according to an embodiment of the present invention may include a polymer. For example, the polymer may correspond to an amine polymer. The amine polymer may be any one of a primary amine, a secondary amine, and a tertiary amine, or a combination thereof.
[0098] In one embodiment, the stability of hole transport materials and even the stability of perovskite optical devices can be greatly improved by using large cations contained in bases such as amine polymers (e.g., primary amines, secondary amines, or tertiary amines). This may be related to the following reasons: according to the "steric effect", large cations such as amine polymers move much slower in solid films than small cations such as lithium ions contained in previous LiTFSI.
[0099] According to one embodiment of the present invention, the acid-base byproduct may be the acid-base byproduct CH3(CH2)7NH3 produced by the reaction of CH3(CH2)7NH2 and HTFSI. + TFSI - , which itself has good dispersibility in organic solvents, can be doped in PTAA to provide high-efficiency PSCs.
[0100] According to one embodiment of the present invention, the concentration of the acid-base byproducts can reach 0 to 3 equivalents relative to PTAA.
[0101] According to one embodiment of the present invention, a hole transport layer doped with acid-base byproducts can be formed using a solution method. For example, PTAA is dissolved at a concentration of 10 mg / mL using toluene, chlorobenzene or chloroform as a solvent, and 0.8 mg of CH3(CH2)7NH2 (base) and 1.7 mg of HTFSI (acid) are added to make a mixture solution. The mixture solution can be spin-coated on the perovskite film to form a hole transport layer.
[0102] Example 1: FTO (TEC8) / mp-TiO2 / perovskite / PTAA (acid-base byproduct) / Au
[0103] According to the optical device of embodiment 1 of the present invention, Figure 2 As shown, it has a bi-layer structure. Specifically, the optical device includes a doped FTO (TEC8) / mp-TiO2 / perovskite (Perovskite) / acid-base byproduct CH3 (CH2) 7NH3 + TFSI - of PTAA / Au.
[0104] Comparative Example 1: FTO (TEC8) / mp-TiO2 / Perovskite / PTAA (LiTFSI, tBP) / Au
[0105] According to the optical device of Comparative Example 1, Figure 1 As shown, it has a bi-layer structure. Specifically, the optical device includes PTAA / Au doped with FTO (TEC8) / mp-TiO2 / perovskite / LiTFSI and tBP.
[0106] Performance Comparison
[0107] Using the perovskite optical devices prepared by the above-mentioned Example 1 and Comparative Example 1, the performance of the optical devices was evaluated by the following method, and the results are shown in Tables 1 to 3 below.
[0108] 1) Current-voltage characteristics: The open circuit voltage (VOC), short circuit current density (JSC) and fill factor (FF) were measured using an artificial solar energy device (ORIEL class A solar simulator, Newport, model 91195A) and a source-meter (Kethley, model 2420).
[0109] 2) Power conversion efficiency (PCE): Under constant temperature and humidity conditions of a sunlight intensity of 1000 W / ㎡, a temperature of 85°C and a humidity of 85%, the perovskite optical device prepared in Example 1 and Comparative Example 1 was exposed to a light source with a wavelength of 280 to 2500 nm, and the PCE value was measured.
[0110] 3) Stability: The measured PCE value was substituted into the following formula to evaluate the stability.
[0111] Formula=(η1 / η0)x100
[0112] Where η0 is the initial photoelectric conversion efficiency of the perovskite optical device just after the stability test, and η1 is the photoelectric conversion efficiency of the same perovskite solar cell after exposure to 85°C and 85% for 100 hours.
[0113] 4) Charge transport properties of the hole transport layer according to additives: The charge transport properties of the hole transport layer (Example: PTAA) according to additives were measured by current-voltage characteristics (refer to Figure 3 ).
[0114] Table 1
[0115] Efficiency comparison of photoelectric conversion devices
[0116] <![CDATA[J sc (mA / cm 2 )]]> <![CDATA[V oc (V)]]> FF PCE(%) Comparative Example 1 26 1.05 81 22.11 Example 1 26 1.06 84 23.15
[0117] From Table 1, it can be confirmed that the photoelectric conversion device according to Example 1 shows higher power conversion efficiency than that of Comparative Example 1.
[0118] Table 2
[0119] Comparison of stability of photoelectric conversion devices (85°C, 85% efficiency after 100 hours)
[0120] Initial efficiency Ultimate efficiency Efficiency maintenance rate (%) Comparative Example 1 22.11 20 90.45 Example 1 23.15 23 99.35
[0121] From Table 2, it can be confirmed that the photoelectric conversion device according to Example 1 has significantly improved device stability compared with Comparative Example 1.
[0122] Table 3
[0123] Charge transport properties of PTAA (ref. Figure 3 )
[0124] Resistance(Ω) Conductivity(S) PTAA alone (without dopant) 251M 3n Comparative Example 1 (Conventional Dopant) 26M 38n Example 1 (New dopant) 1M 1000n
[0125] In Table 3, the charge transport characteristics according to the doping ability of the hole transport layer are expressed as resistance values and conductivity values. Referring to Table 3, it can be confirmed that the PTAA according to Example 1 has significantly improved charge transport characteristics compared with the undoped PTAA of Comparative Example 1.
[0126] The preferred embodiments of the present invention described above are disclosed for illustrative purposes only, and those skilled in the art with ordinary knowledge may make various modifications, changes and additions within the spirit and scope of the present invention, and these modifications, changes and additions should be deemed to be within the scope of the claims.
[0127] A person skilled in the art who has ordinary knowledge in the field to which the present invention belongs may make various substitutions, deformations and modifications without departing from the technical spirit of the present invention, and therefore the present invention is not limited to the above-mentioned embodiments and drawings.
Claims
1. An organic hole transport material doped with acid-base byproducts, characterized in that: The acid-base byproduct corresponds to CH3(CH2)7NH3 + TFSI - , The organic hole transport material corresponds to PTAA.
2. An optical device, characterized in that: The optical device comprises the organic hole transport substance according to claim 1.
Citation Information
Patent Citations
Organic semiconductor doping process
US20160126020A1